Ethnography and Development : the Work of Richard F. Salisbury (Fontanus monograph series., 2004)
Richard Salisbury (1926-1989) was a pioneer in development anthropology and one of the founders of McGill University's anthropology department. His work had immense influence in the areas of economic anthropology, ethnographic practice (New Guinea, northern Canada) and policy formation. This volume commemorates and explores his life and work. Ethnography and Development presents eighteen articles written by Salisbury between 1954 and 1988, framed by seven original essays that explore his basic ideas as well as the intellectual and personal contexts in which he worked. The articles and essays highlight many of the issues that informed those of his generation who worked in economic and political anthropology, the anthropology of development, public anthropology, advocacy and applied anthropology, and in developing the organisational vehicles on which the profession currently depends. Salisbury's broad socio-economic vision, conceptual ideas, and socio-cultural ethnographic theories continue to exert a powerful influence on the discipline. Contributors include Harvey A. Feit (McMaster University), Henry J. Rutz (Hamilton College), and Colin H. Scott (McGill University).